Directives, strategies, plans, projects versus reality about waste management in EU and Romania - Csaba Nagy (Analele Universitatii "Eftimie Murgu" Resita: Fascicola II, Studii Economice, 2020)
Waste management, also known as waste management, refers to education on waste collection, transport, treatment, recycling and storage. Usually, the term refers to materials resulting from human activities and reducing their effect on human health, the environment, or the appearance of a habitat. Waste management also aims to save natural resources by reusing recoverable parts. Managed waste can be both solid and liquid or gaseous, as well as with various properties, requiring treatment methods specific to each. In Romania, the waste management activity is based on Law 211/2011, which implements a series of Council of Europe directives. The coordination of this activity is the responsibility of the Ministry of Environment and the National Agency for Environmental Protection (ANPM). From an economic point of view, the waste management activity in Romania has a share of EUR 10 billion.